The Larvae Stage of Thai Freshwater Pearl Mussel, Hyriopsis (Hyriopsis) bialatus Simpson 1900 Morphological Development - Kovitvadhi, Uthiwan; Kovitvadhi, Satit; Youngsabanant, Mayuva (Thai Journal of Science and Technology, 2024)
Glochidia of Thai freshwater pearl mussel, Hyriopsis (Hyriopsis) bialatus was cultured in artificial medium consisting of M199, fish plasma (Cyprinus carprio), and antibiotics/antimycotic at a ratio of 2:1:0.5 (V/V). They were reared at a density of 50 - 100 glochidia per dish under sterile conditions until they transformed into juveniles. The culture dish was incubated at 23±2°C with a constant supply of 5% CO2. The duration of glochidia development until the juvenile stage was 10 days. After transformation, early juvenile mussels were reared and fed with a mixture of 4 types of phytoplankton (Chlorella sp.2., Kirchneriella incuvata, Navicula sp. and unknown) until 15 days. The morphological study of glochidia and early juveniles were carried out using light and scanning electron microscope. The results illustrated that glochidia and early juvenile cultured in artificial medium exhibited normal morphological development and could undergo normal transformation. The appearance of primitive gills, foot, gastrointestinal tract, and growth lines on the shell are signs of complete metamorphosis.